Enhancing lutein production with mixotrophic cultivation of Chlorella sorokiniana MB-1-M12 using different bioprocess operation strategies. (April 2019) - Chen, Jih-Heng; Chen, Chun-Yen; Hasunuma, Tomohisa; Kondo, Akihiko; Chang, Chien-Hsiang; Ng, I-Son; Chang, Jo-Shu
Graphical abstract: Highlights: A mutant strain C. sorokiniana MB-1-M12 was cultivated outdoors for lutein production. Lutein production is better with semi-continuous operation compared to fed-batch operation. Simulated outdoor cultivation yielded a high lutein productivity of 3.34 mg/L/d. Productivity was enhanced to 4.46 mg/L/d in outdoor cultivation with 60 L PBRs. Strain MB-1-M12 is suitable for outdoor large-scale cultivation for lutein production. Abstract: A lutein-enriched mutant, Chlorella sorokiniana MB-1-M12 was grown mixotrophically for lutein production. The lutein production efficiency of the strain was enhanced via optimizing the operating strategies. The results show that using semi-continuous cultivation with a medium replacement ratio of 75% resulted in a higher lutein productivity and lutein concentration of 6.24 mg/L/d and 50.6 mg/L, respectively, which were markedly higher than those obtained from batch and fed-batch cultivation. Cultivation under simulated outdoor cultivation conditions (i.e., temperature of 35 °C/25 °C for a 12 h/12 h light/dark cycle) could achieve the highest lutein productivity and lutein concentration of 3.34 mg/L/d and 30.8 mg/L, respectively. Lutein production via outdoor cultivation of MB-1-M12 strain with a 60-L tubular photobioreactor was performed using semi-continuous operation. With a medium replacement ratio of 75%, a good lutein productivity (4.46 mg/L/d) and concentration (27.4 mg/L) was obtained, indicating the feasibility of producing lutein under outdoor cultivation of the microalgal strain.